2006
DOI: 10.1080/15216540500507408
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory activity of chlorogenic acid on enzymes involved in the fatty acid synthesis in animals and bacteria

Abstract: SummaryIt was found that chlorogenic acid inhibited in vitro animal fatty acid synthase (FAS I) and the b-ketoacyl-ACP reductase (FabG) from Escherichia coli in a concentration-dependent manner with respective IC50 of 94.8 and 88.1 mM. The results of LineweaverBurk plots indicated that chlorogenic acid inhibited competitively the binding of NADPH to FAS I, while left those of acetyl-CoA and malonyl-CoA unaffected. Further kinetic studies showed that chlorogenic acid blocked the activity of FAS I mainly by inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 34 publications
(33 reference statements)
0
23
2
Order By: Relevance
“…Our preliminary results showed that PJT was rich in polyphenol, which inhibits lipase to reduce lipid absorption, as suggested for tea catechins 20 . Furthermore, several lines of in vitro studies have demonstrated the occurrence of hypolipidemic compounds in PJT leaves 9,10 . It is, therefore, likely that these active components may infl uence the lipid dynamics, in concert, to prevent the mice from developing obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary results showed that PJT was rich in polyphenol, which inhibits lipase to reduce lipid absorption, as suggested for tea catechins 20 . Furthermore, several lines of in vitro studies have demonstrated the occurrence of hypolipidemic compounds in PJT leaves 9,10 . It is, therefore, likely that these active components may infl uence the lipid dynamics, in concert, to prevent the mice from developing obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Antibacterial activities of hydro-distilled essential oils of whole parts of P. japonicum indicating anti-inflammatory and potential health benefits on human skin have been reported (Yang et al 2009). Furthermore, several in vitro studies have demonstrated the occurrence of hypolipidaemic compounds in leaves of P. japonicum (Hsu and Yen 2007; Li et al 2006). While studying the radical scavenging activity of P. japonicum , (Hisamoto et al 2003) isolated 17 compounds from the leaves, of which several compounds played an important role in the potent antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in the serum and hepatic triglyceride levels in CBE-fed rats is thought to be induced by both the suppression of fatty acid synthesis in hepatic cytosol and the acceleration of fatty acid oxidation in hepatic mitochondria. Chlorogenic acid has been shown to inhibit FAS activity (Li et al, 2006), while there are few reports that caffeine affects the activities of fatty acid synthetic enzymes. Therefore, chlorogenic acid in CBE may be responsible for the suppression of fatty acid synthesis in the liver.…”
Section: Cumulationmentioning
confidence: 99%